Mathematical modelling of the population impact of screening for Chlamydia Trachomatis and Neisseria gonorrhoeae in South Africa - Esra, Rachel (Department of Public Health and Family Medicine, 2019)
A large proportion of chlamydial and gonococcal infections are asymptomatic. In lower- and middle-income countries like South Africa, where syndromic management is practiced, it is likely that a large proportion of curable STIs go untreated, as screening for asymptomatic STIs is rarely conducted. Due to the lack of empirical data on the efficacy of STI screening programs, dynamic mathematical modelling has been used to assess the impact of screening, but most previous modelling studies have focused on high-income settings. Here we utilize dynamic mathematical modelling to evaluate the potential impact of opportunistic STI screening programs on the incidence and prevalence of Chlamydia trachomatis and Neisseria gonorrhea in South Africa. We extended an existing agent-based model of heterosexual HIV and STI transmission in South Africa to investigate the impact of targeted screening strategies directed at high risk groups including youth, female sex workers, pregnant women and patients in HIV care. All four screening strategies resulted in reductions in general and key population STI transmission. Opportunistic STI screening of youth and ART patients were shown to be most effective and represent viable interventions for reducing STI transmission in the South African population. Additionally, we compared the modelled impact of a standardized screening program to results obtained from other published mathematical models of chlamydia screening. Differences between models could be attributed to differences in the modelled heterogeneity in sexual behaviour as well as differences in assumptions about immunity following chlamydia recovery.